2001
DOI: 10.1080/016502501316934851
|View full text |Cite
|
Sign up to set email alerts
|

The role of parental perceived control in child development: A longitudinal study

Abstract: The study investigated the role of parental perceived control in child development. A discussion of the conceptual bases of two parental locus-of-control scales led to differential predictions as regards their relations with parent experiences during infancy and child problems and competencies at 4 and 9 years. The Parental Control of Child’s Behaviour scale was suggested to measure perceived control and to be related to infancy factors and child outcomes. The Parental Responsibility scale was tentatively seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 39 publications
9
77
0
2
Order By: Relevance
“…One recent study found that self-effi cacy mediated the effects of child behavior problems on anxiety and depression in mothers of children with special needs (Hastings & Brown 2002). Other studies (Hagekull 2001;Wiggs & Stores 2001) on the sense of control parents have shown that low personal control is associated with higher parenting stress and psychological distress. Weiss et al (2013) found perceived self-effi cacy and social support mediated the link between the pile-up of stressors and family hardiness, and that hardiness was a partial mediator in explaining how stressors were associated with family distress.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that self-effi cacy mediated the effects of child behavior problems on anxiety and depression in mothers of children with special needs (Hastings & Brown 2002). Other studies (Hagekull 2001;Wiggs & Stores 2001) on the sense of control parents have shown that low personal control is associated with higher parenting stress and psychological distress. Weiss et al (2013) found perceived self-effi cacy and social support mediated the link between the pile-up of stressors and family hardiness, and that hardiness was a partial mediator in explaining how stressors were associated with family distress.…”
Section: Introductionmentioning
confidence: 99%
“…Negative parent-referent attributions have been linked to unsatisfying parenting experiences (Hageskull, Bohlin, & Hammarberg, 2001), childhood behavior problems (Hageskull et al, 2001;Johnston, Hommersen, Seipp, 2009), and more authoritarian or permissive styles of parenting (Leung & Slep, 2006).…”
mentioning
confidence: 99%
“…Furthermore, low perceived control has been connected to coercive and authoritarian caregiving behaviours (Bugental et al, 1989), behaviours that presumably do not exert a positive influence on the child's developing emotion regulation. Low parental perceived control has also been associated with high levels of child externalizing and internalizing behaviour problems both concurrently and prospectively (Campis et al, 1986;Hagekull et al, 2001;Janssens, 1994). These results point to low parental perceived control as an important factor contributing in the development of child problems.…”
Section: Parenting and Emotion Regulationmentioning
confidence: 80%
“…The concept of perceived control refers to a person's beliefs about how much control is available (Skinner, 1996); it taps the subjective experience rather than the actual degree of control. More infant negative emotionality predicted low parental perceived control in the preschool age (Hagekull et al, 2001). Furthermore, low perceived control has been connected to coercive and authoritarian caregiving behaviours (Bugental et al, 1989), behaviours that presumably do not exert a positive influence on the child's developing emotion regulation.…”
Section: Parenting and Emotion Regulationmentioning
confidence: 97%